2022
DOI: 10.1007/s13246-022-01130-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of field of view size and reconstruction methods on single-energy metal artifact reduction: a phantom study

Abstract: The purpose of this study was to evaluate the effect of single-energy metal artifact reduction (SEMAR) for metal artifacts using CT images reconstructed with adaptive iterative dose reduction three dimensional (AIDR3D) and advanced intelligent clear-IQ engine (AiCE) in calibration-eld of view of various sizes. A prosthetic hip joint was arranged at the center of the phantom. The phantom images were scanned by changing calibration-eld of view of 320 mm and 500 mm, and were reconstructed using ltered back-projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous studies showed it embraces many outstanding advantages such as enhancing density and spatial resolution, reducing artifacts and noise, and creating extraordinarily high-quality images without increasing radiation dose [ 22 24 ]. In a phantom study, AiCE plus SEMAR performed the best in reducing artifacts compared to other algorithms [ 25 ]. Moreover, studies have shown that combining DLR with SEMAR further reduces image noise and artifacts, thus improving image quality, in CT images with metal implants [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed it embraces many outstanding advantages such as enhancing density and spatial resolution, reducing artifacts and noise, and creating extraordinarily high-quality images without increasing radiation dose [ 22 24 ]. In a phantom study, AiCE plus SEMAR performed the best in reducing artifacts compared to other algorithms [ 25 ]. Moreover, studies have shown that combining DLR with SEMAR further reduces image noise and artifacts, thus improving image quality, in CT images with metal implants [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AiCE reconstruction technique has improved image noise and enables a reduction of radiation dose maintaining image quality compared to CT images using conventional iterative reconstruction (IR). It has been reported that AiCE is useful in various regions such as chest, cardiac, abdomen, CT angiography, and orthopedics [8][9][10][11][12][13][14]. However, it is not clear whether extensor tendons CT images reconstructed using AiCE enable a decrease in image noise and a reduction of radiation dose to better identify extensor tendons on 3D images.…”
Section: Introductionmentioning
confidence: 99%